The logic of categorisation in sport - Parry, J.; Martínková, I. (European Journal of Sport Science, 2021)
1. Categorisation - the Desirability Condition 2. Arbitrary Rules, Discrimination and Decision-making 3. Category Enforcement and Category Cheating 4. Inclusion and exclusion 5. Rights - `Eligibility` claims and `Inclusion` claims. 6. Fairness - 'Competition advantage' and 'category advantage' 7. Concluding Remarks